The Montessori Approach as a Model of Personalized Instruction - Marusa Mavric (University of Kansas, 2020)
I present a brief overview of the key elements of personalized learning and Montessori education, a related pedagogical approach, aiming to examine common theoretical principles and key elements. I discuss the common features of personalized instruction and the Montessori approach of education. Both personalized instruction and the Montessori approach stand firmly on a constructivist paradigm and share many philosophical and theoretical principles. Research has shown that Montessori education is one of the most visible models that incorporates numerous aspects of personalized instruction and shares many common elements with personalized learning. This research has shown that, while personalized instruction also suggests many strategies for implementation of the concept, Montessori education actualizes the principles of personalized learning.